Entrepreneurial Ecosystems and Sustainable SME Growth in Ghana: The Mediating Role of Innovation Capability (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Small and Medium Enterprises (SMEs) are foundational to economic development in Sub-Saharan Africa, yet their sustainable growth potential remains persistently constrained by inadequate ecosystem conditions and limited innovation capacity. This study investigates how entrepreneurial ecosystems, operationalized through six dimensions comprising community support, university support, government support, access to finance, institutional quality, and infrastructure, influence sustainable SME growth in Ghana, with innovation capability serving as a mediating mechanism and entrepreneurial purpose as a moderating variable. Grounded in Dynamic Capabilities Theory and the Resource-Based View, a quantitative cross-sectional survey design was employed, gathering data from 350 SME owners and managers across selected regions of Ghana. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied for hypothesis testing. Measurement model assessment confirmed strong construct reliability (Cronbach's α range: 0.80–0.91; composite reliability range: 0.85–0.93), adequate convergent validity (AVE range: 0.55–0.65), and acceptable discriminant validity, with all Heterotrait-Monotrait (HTMT) ratios below the 0.85 threshold. The structural model explained 72.4% of variance in innovation capability (R² = 0.724) and 67.1% of variance in sustainable SME growth (R² = 0.671), with predictive relevance confirmed (Q² = 0.463 for innovation capability; Q² = 0.407 for sustainable SME growth). Model fit was acceptable (SRMR = 0.058; NFI = 0.908). The findings confirm that all six ecosystem dimensions directly and positively influence both innovation capability and sustainable SME growth. Innovation capability significantly mediates the relationship between the entrepreneurial ecosystem and sustainable SME growth, while entrepreneurial purpose positively moderates the innovation capability–sustainable growth nexus. This study extends entrepreneurial ecosystem literature to the Sub-Saharan African context and provides actionable insights for policymakers, university administrators, and SME practitioners seeking to foster innovation-driven sustainable growth in developing economies.